Rozwiązane

a 2x + 5 = 7 6,1,-1

b 2- 4x = 6 -1,0,1

c x - 7 = -9 1,2,-2

d 2x + 3 = 7 5,2,-2
daje naj



Odpowiedź :

Odpowiedź:

a 2x + 5 = 7     x= 6,1,-1

x= 6  12+5=7  17[tex]\neq[/tex]7

x= 1  2+5=7     7=7

x= -1  -2+5=7  3[tex]\neq[/tex]7

b 2- 4x = 6      x= -1,0,1

x= -1   2+4=6    6=6

x= 0   2-0=6    2[tex]\neq[/tex]6

x= 1   2-4=6    -2[tex]\neq[/tex]6

c x - 7 = -9      x= 1,2,-2

x= 1    1-7=-9     -6[tex]\neq[/tex]-9

x= 2   2-7=-9      -5[tex]\neq[/tex]-9

x= -2   -2-7=-9    -9=-9

d 2x + 3 = 7      x= 5,2,-2

x= 5   10+3=7    13[tex]\neq[/tex]7

x= 2    4+3=7     7=7

x= -2    -4+3=7   -1[tex]\neq[/tex]7